Exploring New Zealand Honeydew Honey, Yacon Concentrate, and their Novel Food and Health Applications - Chessum, Keegan (Auckland University of Technology, 2025)
In order to understand the physical and functional properties of food products, it is essential to obtain physicochemical and sensory information. Without this information, it would be impossible to establish market opportunities, as manufacturers and researchers would be unable to predict consumer acceptance. In this thesis, physicochemical principles were used to understand the properties of New Zealand honeydew honey (NZHDH) and New Zealand yacon concentrate (NZYC). Subsequently, NZHDH and NZYC were incorporated into a novel food product (low alcohol beer), which was analysed using both physicochemical principles and sensory evaluations. Finally, alternative applications of NZHDH and NZYC were investigated, including their inhibitory effects on the formation of acrylamide, their anti-diabetic and anti-obesity properties, and their anti-microbial properties. In Chapter 3, the physicochemical properties of NZHDH such as proximate composition, mineral, sugar, phenolic, and amino acid profiles, and antioxidant activity, were determined. Results indicated the major mineral in NZHDH was potassium, with significant amounts of phosphorus, magnesium, and sodium. The major sugars were fructose and glucose, while sugars unique to NZHDH such as palatinose, turanose, erlose, and melezitose were also detected, with erlose dominating over melezitose. The major phenolic compounds were pinocembrin, abscisic acid, and pinobanksin, with this being the first comprehensive phenolic profiling of NZHDH conducted to the author’s knowledge. Proline was the major amino acid; L-aspartic acid, L-glutamic acid, L-alanine, and L-phenylalanine were the next most abundant, with this being the first profiling of the amino acid content of NZHDH to the author’s knowledge. The antioxidant activity of NZHDH was comparable to literature values for Mānuka honey, considered to be the “gold standard” for antioxidant activity. Overall, NZHDH was comparable to other more well-described varieties of HDH in the literature, suggesting it would have similar health-promoting benefits. In Chapter 4, the physicochemical properties of NZYC such as proximate composition, mineral, sugar, phenolic, amino acid, and organic acid profiles, antioxidant activity, and glycaemic index (GI), were determined. Results indicated that the major mineral in NZYC was potassium, with significant amounts of phosphorus, calcium, and magnesium also identified. Fructose was the major sugar; NZYC was also found to have high total content of fructooligosaccharides (FOS) and inulins (non-digestible prebiotic carbohydrates) which have been associated with numerous health benefits including gut health and weight loss, among others. Chlorogenic acid and caffeic acid were the major phenolic compounds; L-arginine, L-glutamic acid, L-proline, L-aspartic acid, and asparagine were the major amino acids; citric acid was the major organic acid. The antioxidant activity of NZYC was found to be several times higher than Mānuka honey, and NZYC was determined to be a low-GI food. Overall, these results indicate that NZYC may have excellent health-promoting benefits, particularly in the areas of gut health, weight loss, and antioxidative effects. In Chapter 5, five novel flavoured low alcohol beers (LABs) (and one control beer) incorporating NZHDH and/or NZYC were developed. The physicochemical properties of these LABs such as ethanol content, fructooligosaccharide and inulin presence, volatile profile, colour, and amino acid profile were determined. All six LABs had sufficiently low ethanol content to be classified as LABs in New Zealand. Beers that were flavoured with NZYC were found to contain fructooligosaccharides and/or inulins, while beers which were not flavoured with NZYC were not. The LABs could not be differentiated in terms of their volatile profile; however, crude NZHDH was found to differ from crude NZYC, particularly due to the presence of compounds associated with “earthy” flavours. Significant differences were not consistently identified across all LAB samples in terms of colour; however, samples containing NZYC tended to have darker colour than samples which did not. The LABs could not be differentiated in terms of their amino acid profiles. Sensory evaluation of the LABs was also conducted using unstructured line scales, just-about-right (JAR) scales, and check-all-that-apply (CATA) questions. Fifty-three participants completed the sensory evaluation (thirty-one male and twenty-two female). For unstructured line scales, the LAB samples could not be differentiated but were overall somewhat liked by the participants. For JAR, three attributes were evaluated and a high proportion of participants indicated that sweetness, hoppiness, and bitterness were too low in the six LAB samples. Twenty-six terms were used for CATA, and seven of these terms reached statistical significance between the LAB samples. Results from physicochemical analysis supported the incorporation of NZYC into a functional LAB beverage; however, both physicochemical and sensory results suggest that reformulation would be required to achieve greater differentiation between the samples and increased overall liking. In Chapter 6, the potential health benefits of NZHDH and NZYC were investigated with respect to inhibition of the formation of acrylamide in the Maillard reaction, anti-diabetic and anti-obesity activity, and anti-bacterial activity. Results suggest that NZHDH, NZYC, and phenolic compounds found in NZHDH and NZYC are unable to significantly reduce the formation of acrylamide at the tested concentrations. Phenolic extracts of NZHDH and NZYC were found to exhibit anti-diabetic activity, which was in agreement with literature concerning the major phenolic compounds identified in Chapters 3 and 4. Crude NZYC was found to exhibit anti-obesity activity, which was in agreement with literature concerning the major phenolic compounds identified in Chapter 4, while crude NZHDH exhibited negligible anti-obesity activity. Phenolic extracts of NZHDH and NZYC were unable to inhibit the growth of Escherichia coli, Pseudomonas aeruginosa, or Saccharomyces cerevisiae. Overall, this thesis provides insightful information regarding (a) physicochemical information on NZHDH, NZYC, and novel LAB beverages formulated containing NZHDH and/or NZYC, (b) sensory information on the novel LAB beverages, and (c) some potential health benefits of NZHDH and NZYC. In terms of the practicality of the research, manufacturers and researchers now have basic physicochemical information about NZHDH and NZYC, some of which was not previously available in the literature, while NZYC has been highlighted due to its high FOS content and notable anti-obesity effects. Further experimentation should be considered such as reformulation of the LABs to improve functional properties, sample differentiation, and overall liking.